Enterprise artificial intelligence transformation : a playbook for the next generation of business and technology leaders - Haq, Rashed (John Wiley & Sons, Inc., 2020)
"Enterprise Artificial Intelligence Transformation helps business and technology professionals master the segments of the AI market that relate to them and achieve, maintain, and grow successful and cost-effective AI. Readers will learn to build and sustain an AI organizational capability at scale. The author takes a dual analytic and instructional approach, enabling readers to come away confident in their ability to utilize AI effectively. Topics covered include: Crafting an AI strategy Machine learning, deep learning, and semantic modeling Creating and managing an AI Center of Excellence Risk management, and Real-world AI use cases"--